Introduction to Engineering Thermodynamics - Yu Yan, Claire (Open textbook library., 2022)
The book is most suitable for a one-term, introductory engineering thermodynamics course at the undergraduate level. It may also be used for self-learning of fundamental concepts of classical thermodynamics.